The Relationship Between Waist-Hip Ratio And The Severity Of Primary Dysmenorrhea Among Undergraduate Midwifery Students - Diyah Sulistiyorini; Arifiandi Maya Devi; Kentri Anggarina Gumanti (Citra Delima Scientific journal of Citra Internasional Institute, 2026)
Primary dysmenorrhea is common among women, with a prevalence of primary dysmenorrhea in East Java is approximately 54.89% of the total 64.25% of dysmenorrhea cases. Central obesity is thought to increase prostaglandin production, which may potentially exacerbate menstrual pain. Waist-hip ratio is a simple indicator of central obesity; however, evidence regarding its association with the severity of primary dysmenorrhea remains inconsistent. This study aimed to determine the relationship between waist-hip ratio and the degree of primary dysmenorrhea among undergraduate midwifery students at the Faculty of Medicine, Universitas Brawijaya Malang. This study employed a cross-sectional design. A total of 72 undergraduate midwifery students from the class of 2023 who experienced primary dysmenorrhea were selected as the sample using total sampling. Waist-hip ratios were measured using a measuring tape, while the severity of dysmenorrhea was assessed using the Numerical Rating Scale (NRS). The data were analyzed using Spearman’s rank correlation. The analysis showed a significance value of 0.454 (p > 0.05) and the correlation coefficient (r) is 0.090, indicating that no statistically significant relationship was found between waist-hip ratio and the severity of primary dysmenorrhe among undergraduate midwifery students at the Faculty of Medicine, Universitas Brawijaya Malang. This study suggests that future research should select a sample with abnormal waist-hip ratios, control for confounding factors, and take measurements when respondents are experiencing dysmenorrhea.